TINGKAT KESUKAAN CHOUX PASTRY KERING DENGAN SUBSTITUSI TEPUNG IKAN GABUS - Esthy Rahman Asih; Yuliana Arsil (POLTEKKES KEMENKES MANADO, 2020)
One of the local food ingredients that can be used as a source of protein is cork fish. Cork fish can be processed into flour, which can reduce damage and increase added value. This fish meal can be prepared into various snacks, one of which is a crispy choux pastry. Higher protein content with the substitution of cork fish flour in this crispy choux pastry has the potential to be a high-protein snack. This study aims to determine the sensory evaluation of crispy choux pastry formulation with cork fish meal substitution. The experimental design used in this study was CRD (Complete Randomized Design). The formulation of cork fish meal substitution in the production of crispy choux pastry is 0, 15, 30 and 45%. The resulted choux pastry was tested on the sensory evaluation at 30-semi-trained panellists. The results showed that the substitution of cork fish flour had a significant effect on the color, aroma and texture preference parameters. The substitution of cork fish flour in making crispy choux pastry by 15% is the best treatment with a color preference level value (5.80); taste (5,33); aroma (5,27); and texture (6.53).